Problems In The Execution Of Administrative Court Decisions In Employment Disputes - David Pasaribu; Irene Cristna Silalahi (PT Justitia Legal Research, 2026)
The Administrative Judiciary (Peratun) plays an important role in resolving disputes between citizens and government agencies/officials, including employment disputes. However, in practice, it is often the case that Peratun decisions that have permanent legal force are not voluntarily implemented by government agencies/officials. This results in several problems, including a decline in the court's authority and a loss of public confidence. One of the main causes is non-compliance by officials. In addition, the lengthy dispute resolution process, especially with ordinary proceedings, often makes it impossible to enforce the decision, because the plaintiff has reached retirement age, their term of office has expired, or their position has been filled by someone else. This normative study found that the expedited examination mechanism stipulated in Law Number 5 of 1986 on Administrative Courts and its amendments (Peratun Law) only applies at the first level, so that the appeal and cassation processes still take a considerable amount of time. Another factor is the absence of coercive measures such as those found in the general courts. Enforcement in the Administrative Court relies solely on coercive fines and/or administrative sanctions, so that the Administrative Court often has to rely on the superiors of the defendant, up to the President and the House of Representatives, to urge the implementation of the decision. To overcome this, it is necessary to limit legal remedies, create synergy between the judiciary and the executive, and improve the quality of the decisions themselves, which must be based on philosophical, sociological, and juridical aspects.